Implementasi Metode Weighted Product dalam Sistem Pendukung Keputusan Pemilihan Mata Kuliah Kelas TI Semester 4 - Felani, Rani Okta; Wicaksono, Anung Amarto; Aminah, Siti (sudo Jurnal Teknik Informatika, 2025)
The selection of courses that are of interest to students is an important factor in increasing learning motivation, academic achievement, and readiness to face the world of work. This study aims to determine the most favorite courses in the Information Technology class of semester 4 of Universitas PGRI Silampari using the Weighted Product (WP) method, one of the approaches in Multi-Criteria Decision Making (MCDM). The assessment is based on four main criteria: student interest, understanding of the material, relevance to the world of work, and the quality of lecturers' teaching. Data were obtained from the results of questionnaires filled out by 19 respondents, then processed quantitatively using the WP method. The results showed that the Mobile Programming course received the highest ranking as the most favorite course, followed by Cloud Programming and Business Intelligence and Big Data. These findings are expected to be input for lecturers and study programs in designing strategies to improve the quality of learning.